A Study of Influence Factors for Advertising on Messaging Applications Towards Mobile Buyer's Decision Making - Paireekreng, Worapat; Osathanukroh, Jaruvarintra; Supasak, Chavanit (International Journal of Informatics and Information Systems, 2019)
The advancement of information technology leads to development of a new business paradigm which is focused on innovative technology. M-commerce seems to be a crucial tool to develop a country rapidly. The combination of messaging application features and business model can build start-up business driven by these technologies. However, the appropriate accessing target group of each business issues to be a main issue in the messaging application usage. This research aims to investigate the influence factors related to advertising on messaging applications. The Mixed method; quantitative and qualitative methods were implemented to investigate such factors. The findings are that three main factors, demographic factors, m-commerce factors, and behavioral factors, affected the buying decision making. Whereas, the demographic factor such as marital status showed no differences in this study. The products such as information technology accessories, beauty products and fashion goods are an important business area for customers focused on m-commerce. In addition, it was found that education had a significant effect towards advertising on messaging applications. Furthermore, the derived influence factors and criteria for advertising on messaging applications were confirmed with online merchants in the focused group method. The main advantage of messaging applications is the ability to interact with merchants and get quick responses. The results can be a guidance for start-up businesses for sustainable development.